Analytical method of multi-mycotoxins in spices for total diet study using liquid chromatography tandem mass spectrometry - Choi Bogyoung; Lee, Youngsun; Kim Jung Hee; PARK, HYUN MEE (AOAC, 2019)
Mycotoxins are natural toxins defined as secondary metabolites produced by fungi species of Aspergillus, Fusarium, and Penicillium. The objective of this study was to develop and validate analytical methods for multi-mycotoxin (aflatoxins, fumonisins, ochratoxin A, and zearalenone) determination in spices for total diet study. Samples were fortified with 13C isotope labeled mycotoxins as internal standard, and extracted with phosphate buffer solution and methanol. Clean-up of the extract was performed by a multi-mycotoxin immunoaffinity column (Myco6in1®), and then analyzed by liquid chromatography/tandem mass spectrometry (LC-MS/MS). Method validation was conducted using red pepper as the representative matrix of spice. Standard curves had a good linearity (R2 > 0.99) in all mycotoxin tested. The method detection limit (MDLs) and method quantification limit (MQLs) for eight mycotoxins ranged from 0.005 to 0.3 ？g/kg and from 0.015 to 0.9 ？g/kg, respectively. The recoveries of all mycotoxins ranged from 89.4 to 117.8% at three concentrations. Intra- and inter-day precisions were in the range of 1.1-10.6% and 1.9-12.3%, respectively. These results are in the acceptable range of Codex Alimentarius Commission (CAC), indicating that these methods are suitable for all mycotoxin determination in several spice samples.